Control of floral meristem activity in the model plant Arabidopsis thaliana - Kwasniewska, Kamila (Trinity College (Dublin, Ireland). Department of Genetics, 2017)
Over the past 30 years, the flower development has been one of the main model to study the genetic control of organogenesis in higher plants. The work on Arahidopsis thaliana has led to the proposal of the ABC model of flower development. This model states the interaction of three classes of the genes that encode transcription factors specifying the four types of organs in the flower, i.e, sepals, petals, stamens and carpels. While the activities of these master regulators have been extensively characterized in recent years, comparatively little is known about the functions of the target genes of these regulators. One of the genes that is acting downstream of AGAMOUS (AG) - the transcription factor that specifies the formation of a carpel, is KNUCKLES {KNU). It has been reported that KNU is directly activated by AG and is believed to be a repressor of WUSCHEL (WUS) activity in the meristematic cells. To fully understand functions of KNU in the stem cells, several transgenic lines were generated. I used approaches allowing for knockdown of KNU functions in different regions of stem cells. I showed, that KNU is expressed earlier in the flower development and interacts with the gene regulating the size of meristem.
Keywords: Genetics & Microbiology, Ph.D.; PhD Trinity College Dublin, 2017